Kolaborasi Pembelajaran Tematik Kontekstual Melalui Kesenian Tari Bali - Gamaliel Septian Airlanda; Ketut Gede Bendesa (Universitas Kristen Satya Wacana Salatiga, 2022)
“Tematik” is the characteristic of education in elementary school in Indonesia. Non-formal education institutions become one of implementer for this learning model. Balinese people have built a kind of this educational perspective using “Balai Banjar” and “Sanggar” (art studio). Sanggar Tari Sekar Dewata is non formal institution which have problems, such as: 1) monotone learning model; 2) locked of human development; 3) high repetitions without innovations; 4) lost human potency. Participatory learning action as the way to higher education researcher become the part of Sanggar community. Its help the researcher to collab and give other perspectives of thematic contextual learning model. Based on this collaboration, founds that: 1) new model of learning give the positive changes; 2) bring the different perspectives of habit-based learning; 3) bring the sustainable collaboration of learning model reconstruction.